Forward momentum: advancing the delivery of pregnancy and postpartum physical activity guidance and support across the island of Ireland - Maria Faulkner; Gráinne M Donnelly; Elizabeth Deery (BMJ Open Sport & Exercise Medicine, 2025)
Physical activity guidance and support for pregnant and postpartum populations across the island of Ireland (Republic of Ireland and Northern Ireland) could be strengthened to better reflect international progress in this area. While Northern Ireland can align with UK guidelines and benefit from initiatives established in mainland UK, the Republic of Ireland has yet to develop updated recommendations or equivalent programmes. Although many pregnant and postpartum individuals know the benefits of physical activity, a significant gap remains in the support they receive to engage in it. While research in this area is emerging in mainland UK, comparable evidence remains limited across the island of Ireland. This underscores the need for policy reforms to embed physical activity guidance into routine maternity care. Eight actionable steps are proposed to address these gaps, with a focus on supporting the timely publication of physical activity guidelines specific to the Republic of Ireland for pregnancy and following childbirth, introducing specialised roles, accredited training and governance structures. These measures aim to empower individuals and professionals, ensuring effective delivery of physical activity support during these critical life stages. By prioritising these changes, the island of Ireland can enhance health outcomes for pregnant and postpartum populations, fostering long-term benefits for maternal and child health.